2019
DOI: 10.1172/jci124725
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-142–mediated repression of phosphodiesterase 3B critically regulates peripheral immune tolerance

Abstract: Tregs play a fundamental role in immune tolerance via control of self-reactive effector T cells (Teffs). This function is dependent on maintenance of a high intracellular cAMP concentration. A number of microRNAs are implicated in the maintenance of Tregs. In this study, we demonstrate that peripheral immune tolerance is critically dependent on posttranscriptional repression of the cAMP-hydrolyzing enzyme phosphodiesterase-3b ( Pde3b ) by microRNA-142-5p (miR-142-5p). In this manner, miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 71 publications
5
46
2
Order By: Relevance
“…Previously, miR-142-5p was found to be tumor-suppressing in lung adenocarcinoma, 28 pancreatic cancer 29 and gastric cancer, 30 and was reported to be cisplatin-related in ovarian cancer. 31 Additionally, miR-142-5p is associated with peripheral immune tolerance, 32 as well as a profibrogenic macrophage program. 33 In the present study, we revealed that miR-142-5p suppresses chondrocyte apoptosis and promotes proliferation.…”
Section: The Regulatory Axis Of Xist/mir-142-5p/sgtb In Il-1β-inducmentioning
confidence: 99%
“…Previously, miR-142-5p was found to be tumor-suppressing in lung adenocarcinoma, 28 pancreatic cancer 29 and gastric cancer, 30 and was reported to be cisplatin-related in ovarian cancer. 31 Additionally, miR-142-5p is associated with peripheral immune tolerance, 32 as well as a profibrogenic macrophage program. 33 In the present study, we revealed that miR-142-5p suppresses chondrocyte apoptosis and promotes proliferation.…”
Section: The Regulatory Axis Of Xist/mir-142-5p/sgtb In Il-1β-inducmentioning
confidence: 99%
“…Interestingly, miR-142-5p, another mature isoform of miR-142, plays a positive role in regulating cAMP-mediated suppressor function of Treg cells. Deleting miR-142-5p decreases the concentration of intracellular cAMP by targeting AMPhydrolyzing enzyme phosphodiesterase-3b (Pde3b), leading to the deficient function of Treg cells and immune disorder in mice despite preserving a number of Treg cells with a normal phenotype(89). miR-99a and miR-150 can target mTOR, which is responsible for cell growth, to promote the differentiation of Treg cells at the expense of inhibiting Th17 cells(90).…”
mentioning
confidence: 99%
“…Paradoxically, the overexpression of miR-142-5p targeting Smad3 has been shown to lead to cancer progression through the suppression of TGF-β-induced growth inhibition in cancer cells [ 10 ]. miR-142-5p is the predominant isoform expressed in thymically derived Tregs and determines peripheral immune tolerance suppressing self-reactive peripheral T effector cell (Teff) responses, thus limiting the development of autoimmunity activity and the upregulation of PDE3B, causing reduced intracellular cAMP and a failure of peripheral tolerance [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, miR-155 upregulates the production of Tregs through the SOCS1. First, Anandagoda reported that miR-142 plays a cell-intrinsic positive role in reinforcing Treg repressive activity [ 13 ]. Previously, Huang et al demonstrated that Teff maintains high levels of the other isoform –3p to limit adenylyl cyclase 9 (AC9) expression, an enzyme fundamental for cAMP production in CD4 + Tcells, thus restricting endogenous cAMP generation.…”
Section: Resultsmentioning
confidence: 99%